Structural evolution in Nanoclay reinforced oilwell cement during Supercritical CO2 (ScCO2) invasion. Issue 7 (October 2021) - Mei, Kaiyuan; Zhang, Liwei; Wang, Yan; Cheng, Xiaowei; Xue, Quan; Gan, Manguang; Fu, Xiaojuan; Zhang, Chunmei; Li, Xiaochun
Abstract: Supercritical CO2 (ScCO2 ) invades oilwell cement and forms carbonate layers in the cement under geological CO2 sequestration conditions. Long-term invasion of ScCO2 makes the carbonation structure unstable and prone to damage. Nanoclay was modified with ScCO2 as the solvent and intercalator for the reinforcement of oilwell cement, forming the microcrystalline Nanoclay (MC Nanoclay). MC Nanoclay is identified and added into the cement slurry to reinforce oilwell cement after the above modification. Microcrystal calcite is found in the MC Nanoclay with transmission electron microscopy (TEM) and selected area electron diffraction (SAED) analyses. Both mechanical properties and microstructural evolution of MC Nanoclay reinforced oilwell cement are investigated, showing that the carbonation was inhibited with MC Nanoclay. With generalized analysis from microcrystal formation and densified carbonation area, the reinforce mechanisms of MC Nanoclay were revealed in this study.